Whatsapp Sebagai Pendidikan Kesehatan Dalam Meningkatkan Pengetahuan Ibu Tentang Mp-Asi - Dwi Ariestantia; Purwaningtias Budi Utami (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
There are various ways to convey information about complementary feeding, including through the delivery of health education with counseling. Extension with the lecture method is the method most often carried out and is limited by time, however the WhatsApp media is a medium of communication that is used daily by many people in almost all countries. The messages sent can be in the form of written messages, images or sounds so that this media is very suitable to be used as a health education medium in order to increase public knowledge in general and especially to mothers about complementary breastfeeding. This study aims to determine the difference in the effectiveness of counseling on complementary foods using lectures and WhatsApp methods at the UPTD Puskesmas Sempaja Samarinda. This research method uses a Quasi-experimental plan with pretest-posttest control group design. This study was conducted on April 3 - 16 2020. The study population was mothers who had children aged 6 months to 2 years. The sample in this study were 66 respondents consisting of 33 intervention groups and 33 control groups. The results of statistical tests show that there are differences before and after giving intervention via WhatsApp with a p-value of 0,000. The conclusion in this study is that there is an increase in respondent knowledge after counseling, but in the intervention group there is a more significant increase in knowledge.